Neurological status of low-risk Vietnamese newborns: a comparison with a British newborn cohort. - Hieu, N; Gainsborough, M; Simpson, J; Thuy, N; Hang, N; Taylor, A; Ghebremeskel, K; Crawford, M; Golfetto, I; Dubowitz, L; Farrar, J (2006)
A shortened version of the Dubowitz newborn neurological examination, recently reassessed in rural Thailand, was applied to a group of 58 Vietnamese newborns. The aim was to establish the neurological status of newborns in this population for use in further studies and to compare with groups previously studied. Compared to the original British cohort, the Vietnamese newborns showed significantly lower scores in 10 of 25 items, including several related to truncal tone. Evidence was sought of thiamine and long-chain fatty acid deficiency as a possible cause for these findings, but no correlation was found between the neurological status and the maternal or infant blood levels of these nutritional indicators. The findings suggest that the neurological status of low-risk Vietnamese newborns appears to lie between that of British newborns and those ethnic minority Karen newborns in refugee camps on the Thai-Burmese border tested previously. Although no specific nutritional cause has been identified in the study, the findings may still reflect sub-optimal intake of some important nutrients.